Optimized algorithm of auxiliary drainage scheme in tailings reservoir rainfall prediction: illustrated with a case study - Mei, Guodong; Wang, Sha; Guo, Lijie (Frontiers in Earth Science, 2023)
Under forecasting rainfall condition, rainfall flows into the tailings pond instantaneously, causing water level rising rapidly, thus threatening the safety of the tailings pond. Therefore, it is of great importance to give auxiliary flood discharge measures in emergency situation. This study investigated the optimized calculation algorithm of two combined schemes of lowering the coverplate of tailing ponds and installing additional drainage pumps to determine the recommended scheme of auxiliary drainage measures for tailing ponds under forecast rainfall and proposed the corresponding prediction and calculation method based on the basic data of the water level-reservoir capacity curve of tailing ponds, forecast rainfall parameters, and flood discharge system parameters. The results showed that compared with the precise algorithm, the optimized algorithm does not need to call the main procedure of flood regulation calculation and is of high calculation efficiency and accuracy, calculation time can be controlled within 0.05s. Through the optimized algorithm, the recommended auxiliary drainage scheme for forecast rainfall can be obtained immediately, which can effectively guide tailing pond flood control and drainage activities during the flood season.